Wear-resistant, self-cleaning and high-definition glass in rain and preparation method thereof
By preparing surface texture and depositing hard films on the glass surface, and adjusting the surface structure using laser scanning technology, the problem of difficulty in achieving wear resistance, self-cleaning and high definition in rain in the glass surface in the prior art is solved, and the wear resistance, self-cleaning and high definition in rain in the glass surface is achieved.
Patent Information
- Application Number
- CN202311288096.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-08
- Publication Date
- 2025-04-08
AI Technical Summary
The prior art is difficult to achieve wear resistance, self-cleaning and high-definition effects of glass surfaces in harsh outdoor environments, especially in heavy rain, where the field of view is easily blocked.
By preparing surface texture on the glass surface and depositing hard films such as silicon carbide, silicon nitride, etc., combined with laser scanning technology, the surface structure and microscopic composition are adjusted to form a wear-resistant, self-cleaning, and high-definition glass surface in the rain.
It achieves extremely strong wear resistance and stability on the glass surface, can maintain a clear field of view in heavy rain, and has self-cleaning performance, reducing maintenance costs.
Smart Images

Figure CN119774889A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of preparation of wear-resistant, self-cleaning and high-definition glass in rain. The corresponding texture is prepared by adjusting the process to achieve the effects of wear-resistant, self-cleaning and high-definition in rain. Specifically, it relates to a wear-resistant, self-cleaning and high-definition glass in rain and a preparation method thereof. Background Art
[0002] Photoelectric screens such as mobile phone screens, computer screens, TV screens, tablet screens, and solar panels are all prone to dust, which seriously affects the user experience. In particular, dust on the surface of solar panels blocks sunlight and reduces power generation efficiency. Studies have shown that if solar cells are not cleaned for three months, the efficiency may drop by 30%. The entire solar cell market is already a trillion-dollar market, and the losses are very large. More seriously, it may cause a hot spot effect, and the blocked cells may be reversely broken down by other batteries in series or even cause fires and other serious consequences. Coupled with the harsh outdoor environment such as wind, frost, rain, snow, dust, etc., it is very important for the glass cover to be wear-resistant and self-cleaning.
[0003] In addition, the hydrophobic glass jointly developed by Fuyao Glass and Volvo has been used in the rearview mirrors of a very small number of high-end models to improve the clarity of cars driving in the rain. The sol-gel method is used to form a fluoride film layer on the glass surface. It is usually tetrafluorosilane, which is expensive and has certain environmental toxicity and pollution. It is not wear-resistant and has poor durability in dusty environments. The video shown on its official website shows that this hydrophobic glass will still block part of the line of sight during the rolling process of water, and may still block the field of vision in heavy rain. Currently, most rainproof films and rainproof agents on the market also use hydrophobic coating technology. The main problem is that the rolling process of water droplets blocks the line of sight.
[0004] Therefore, the glass prepared by the present invention is hydrophilic glass, which has a strong water spreading ability and forms a continuous water film, so that the field of vision is not affected even by heavy rain. At the same time, the surface material of the glass prepared by the present invention is a hard film, which can be a hard material such as diamond-like carbon film, silicon nitride film, aluminum oxide film, silicon carbide film, so the wear resistance and stability are better.
[0005] The present invention attempts to adopt a technology to solve the above-mentioned wear-resistant, self-cleaning, and high-definition glass requirements in rain by adjusting technical parameters. Summary of the invention
[0006] The present invention provides a wear-resistant, self-cleaning, high-definition glass in rain and a preparation method thereof. The surface structure and its microscopic composition are regulated by changing the film thickness, composition and laser scanning parameters of the hard film, thereby achieving the purpose of wear resistance, self-cleaning and high-definition in rain.
[0007] To achieve the above-mentioned object of the invention, the technical solution of the present invention is as follows: The present invention provides a method for preparing wear-resistant, self-cleaning, high-definition glass in rain, comprising the following steps: (1) Preparing surface texture on glass surface; (2) Deposition of hard film on glass surface texture; (3) Laser scanning the glass surface after the hard film is deposited in step (2) to form a micro-nano structure on the glass surface, thereby obtaining wear-resistant, self-cleaning, and high-definition glass in rain.
[0008] Furthermore, the step (1) can be achieved by a sol-gel method, a photolithography method, a reactive ion etching method, a laser ablation method, or a template method.
[0009] Furthermore, the glass includes all glass, glass that can be used in the rain, glass that can be used underwater, and glass that can be used inside the body.
[0010] Furthermore, the hard film includes at least one of silicon nitride film, silicon carbide film, carbon film, titanium carbide film, tungsten carbide film, aluminum nitride film, titanium nitride film, and aluminum oxide film; and the deposition thickness of the inorganic thin film is 1nm-500nm.
[0011] Preferably, the deposition thickness of the inorganic thin film is 2nm-100nm.
[0012] Furthermore, the deposition method includes magnetron sputtering, electron beam evaporation, atomic layer deposition, dip coating, slit coating, and roll-to-roll printing.
[0013] Furthermore, when the deposition method is magnetron sputtering, the typical settings are: RF sputtering of a water-cooled silicon nitride target with a diameter of 60 mm, the sputtering gas is pure Ar, the working gas pressure is 1.6 Pa, the argon gas flow rate is 30 sccm, the power is 60 W, the substrate heating temperature is 250° C., and the deposition time is 2 min.
[0014] In the present invention, different equipment has different process parameters, which can be selected according to actual needs.
[0015] Furthermore, the laser includes at least one of an infrared laser, a visible light laser, an ultraviolet laser, a continuous laser, and a pulsed laser.
[0016] Furthermore, the laser energy density is greater than 50 mJ / cm 2 .
[0017] Preferably, the laser scanning uses a 5W rated power ultraviolet laser. If the laser frequency is 30KHz and the laser spot diameter is 50 microns, the energy density at this time can be estimated to be 8.5 J / cm 2 .
[0018] Furthermore, the laser scanning speed is 0.01 m / s-500 m / s; and the scanning line spacing is ≤10 mm.
[0019] Preferably, the scanning speed of the laser scanning is 0.5 m / s-10 m / s; the scanning power is 1%-100% of the rated power; and the scanning line spacing is 0.1-0.9 mm.
[0020] Furthermore, the wear-resistant, self-cleaning, high-definition glass in rain can be used as both the inner surface and the outer surface of the glass.
[0021] Compared with the prior art, the advantages and beneficial effects of the present invention are: The present invention can achieve wear-resistant and self-cleaning performance by using a simple process, which is superior to the prior art. The prior art mostly uses nano titanium dioxide and glue to adhere to the glass surface. The glue has poor durability and the wear resistance of nano titanium dioxide is not strong. The present invention uses hard films such as silicon carbide, silicon nitride, etc., whose wear resistance far exceeds the prior art.
[0022] The present invention can achieve high definition performance in rain-resistant wear by using a simple process, which is superior to the prior art. The prior art uses a sol-gel method to deposit a layer of fluorosilane on the glass surface, which takes a long time, is costly, and is not durable. The present invention uses a hard film layer, so it has good durability.
[0023] 3. The present invention forms a stable micro-nano structure on the glass surface, achieving a strong water spreading ability on the surface. Therefore, even heavy rain does not affect the field of vision. The prior art uses hydrophobic glass which still blocks part of the field of vision during the water rolling down, and is likely to block the field of vision in heavy rain.
[0024] 4. In terms of technology, the deposition method of the present invention uses magnetron sputtering, electron beam evaporation, atomic layer deposition, dip coating, slit coating, roll-to-roll printing; the requirements for laser scanning are low; the entire preparation method is low-cost and can be completed using industrially stable and mature equipment. Therefore, it can be directly used to produce wear-resistant, self-cleaning, rain-resistant high-definition glass, and has the advantage of large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] FIG1 is a typical laser confocal microscope photo of the reference glass surface after being rubbed by sandpaper in Example 1. Figure 1a For the plan view, Figure 1b The sandpaper friction is to place a 100g weight on a 25mm*50mm glass and drag the weight back and forth on the 180-grit sandpaper for 5 times, and a single trip is 230mm.
[0026] FIG2 is a typical laser confocal microscope photo of the glass surface after being rubbed by sandpaper in process 1 of Example 1. Figure 2a For the plan view, Figure 2b A three-dimensional graph.
[0027] FIG3 is a typical laser confocal microscope photo of the glass surface after being rubbed by sandpaper in process 2 of Example 1. Figure 3a For the plan view, Figure 3b A three-dimensional graph.
[0028] FIG4 is a photograph showing the contact angle measurement of the glass treated by process 1 in Example 1 before and after being rubbed with sandpaper. Figure 4a This is a photo of the contact angle measurement before sandpaper abrasion. Figure 4b This is a photo of the contact angle measurement after sandpaper abrasion.
[0029] FIG5 is a photograph showing the contact angle measurement of the glass treated by process 2 in Example 1 before and after sandpaper abrasion. Figure 5a This is a photo of the contact angle measurement before sandpaper abrasion. Figure 5b This is a photo of the contact angle measurement after sandpaper abrasion.
[0030] Figure 6 This is a comparison of the transmission vision of the glass treated with process 1 and the reference glass in Example 1 after being rubbed with sandpaper and then sprayed with water. After the treatment, the glass water spreads over the entire surface, and there is no water droplet scattering phenomenon. The control glass has a blurred vision in the water spraying experiment.
[0031] Figure 7 This is a comparison of the transmission vision of the glass treated with process 2 and the reference glass in Example 1 after being rubbed with sandpaper and then sprayed with water. After the treatment, the glass water spreads over the entire surface, and there is no water droplet scattering phenomenon. The control glass has a blurred vision in the water spraying experiment.
[0032] Figure 8 This is a comparison chart of the self-cleaning performance of the glass treated with process 1 and the reference glass in Example 1 after being rubbed with sandpaper and then uniformly sprayed with methyl orange and then sprayed with water. No methyl orange remains on the surface of the treated glass. There are more methyl orange droplets on the surface of the reference glass.
[0033] Fig. 9 This is a comparison of the self-cleaning performance of the glass treated with process 2 in Example 1 and the reference glass after being rubbed with sandpaper and then uniformly sprayed with methyl orange and then sprayed with water. There is no methyl orange residue on the surface of the treated glass. There are more methyl orange droplets on the surface of the reference glass.
[0034] FIG10 is a typical laser confocal microscope photo of the treated glass surface after being rubbed with sandpaper in Example 2. Fig.10a For the plan view, Fig.10b A three-dimensional graph.
[0035] Fig.11 This is a comparison of the transmission vision of the treated glass and the reference glass after being rubbed with sandpaper and sprayed with water in Example 2. After the treatment, the water spreads over the entire surface of the glass, and there is no water droplet scattering. The control glass has a blurred vision in the water spraying experiment.
[0036] Fig.12 This is a comparison chart of the self-cleaning performance of the treated glass and the reference glass in Example 2 after being rubbed with sandpaper and then uniformly sprayed with methyl orange and then sprayed with water.
[0037] FIG13 is a typical laser confocal microscope photo of the glass surface after being rubbed with sandpaper in process 1 of Example 3. Fig.13a For the plan view, Fig.13b A three-dimensional graph.
[0038] FIG14 is a typical laser confocal microscope photo of the glass surface after being rubbed with sandpaper in process 2 of Example 3. Fig.14a For the plan view, Fig.14b A three-dimensional graph.
[0039] Fig.15 This is a comparison diagram of the transmission field of view of the glass treated by process 1 in Example 3 and the reference glass after being rubbed with sandpaper and sprayed with water.
[0040] Fig.16 It is a comparison diagram of the transmission field of view of the glass after process 2 treatment in Example 3 and the reference glass after being rubbed with sandpaper and sprayed with water.
[0041] FIG17 is a photograph of the contact angle measurement of the glass treated by process 1 in Example 3 before and after being rubbed by sandpaper, Fig.17a This is a photo of the contact angle measurement before sandpaper abrasion. Fig.17b This is a photo of the contact angle measurement after sandpaper abrasion.
[0042] Fig.18 This is a comparison chart of the self-cleaning performance of the process 1 treated glass and the reference glass in Example 3 after being rubbed with sandpaper and then uniformly sprayed with methyl orange and then sprayed with water.
[0043] Fig.19 This is a comparison chart of the self-cleaning performance of the glass treated with process 2 in Example 3 and the reference glass after being rubbed with sandpaper and then uniformly sprayed with methyl orange and then sprayed with water.
[0044] FIG20 is a typical laser confocal microscope photo of the treated glass surface after being rubbed with sandpaper in Example 4. Fig.20a For the plan view, Fig.20b A three-dimensional graph.
[0045] Fig.21 It is a comparison diagram of the transmission field of view of the treated glass and the reference glass in Example 4 after being rubbed with sandpaper and sprayed with water.
[0046] Fig. 22 This is a comparison chart of the self-cleaning performance of the treated glass in Example 4 and the reference glass after being rubbed with sandpaper and then uniformly sprayed with methyl orange and then sprayed with water. DETAILED DESCRIPTION
[0047] The following embodiments are used to better illustrate the present invention, but the present invention is not limited to the following embodiments.
[0048] Example 1: Preparation of wear-resistant, self-cleaning, rain-resistant high-definition glass based on silicon carbide film The specific steps are as follows: (1) Ultraviolet laser is used to scan soda-lime glass to form texture on the glass surface; the laser rated power is 5W; the scanning process parameters are: scanning speed 3m / s; scanning line spacing 0.03mm; frequency 30KHz; pulse width 8 microseconds. At this time, it is assumed that the energy density when the spot diameter is 50 microns is 5-8 J / cm 2 .
[0049] (2) A silicon carbide film was deposited on the glass that had been laser ablated in step (1) by using a magnetron sputtering coating system. A water-cooled silicon carbide target (99.995%) with a diameter of 60 mm was DC sputtered. The sputtering gas was pure Ar (99.9995%). The working gas pressure was 1.6 Pa. The argon gas flow rate was 30 sccm, the RF sputtering power was 60 W, the substrate heating temperature was 250 °C, and the deposition time was 2 min.
[0050] (3) Ultraviolet laser scanning is used to scan the glass surface after the silicon carbide film is deposited in step (2). A 5W ultraviolet laser is used. Two process parameters are used for laser scanning. One is: frequency 30KHz, pulse width 8 microseconds, scanning speed 3m / s, and scanning line spacing 0.1mm; the other is frequency 30KHz, pulse width 8 microseconds, scanning speed 3m / s, and scanning line spacing 0.7mm. At this time, it is assumed that the energy density is 5 to 8 J / cm when the spot diameter is 50 microns. 2 . Get wear-resistant, self-cleaning, rain-resistant high-definition glass.
[0051] The reference glass and the treated glass were respectively pressed under a 100g weight and dragged back and forth on 180-grit sandpaper for 5 times (the width of the sandpaper is 23cm in one way). Figures 1 and 2 show the surface scratches and micron-level surface morphology information of the reference glass and the glass treated by process 1 after rubbing on sandpaper, and Figure 3 shows the surface scratches and micron-level surface morphology information of the glass treated by process 2 after rubbing on sandpaper. The reference glass surface scratches are deep. The surface of the treated glass is widely distributed with circular pits of varying depths and diameters of about 40 microns. The stripes and circular pits are quasi-periodically distributed, and the surface scratches are shallow. Figure 4 shows the contact angle information of the glass treated by process 1 before and after being rubbed by sandpaper, and Figure 5 shows the contact angle information of the glass treated by process 2 before and after being rubbed by sandpaper. The difference in the contact angle of the glass surface before and after sandpaper rubbing is very small, and it still maintains good hydrophilicity after sandpaper rubbing. Water was sprayed on the glass after sandpaper rubbing to simulate a scene in the rain to observe the clarity in the rain. Figure 6This is a comparison of the glass treated with process 1 and the reference glass after being rubbed with sandpaper and then sprayed with water; Figure 7 This is a comparison of the glass treated with process 2 and the reference glass after being rubbed with sandpaper and then sprayed with water. Compared with the reference glass, the field of view of the treated glass is still clear, while there are many water droplets on the surface of the reference glass and the field of view is blurred. Methyl orange solution is evenly applied on the surface of the glass rubbed with sandpaper and then sprayed with water to observe its surface self-cleaning performance. Figure 8 This is a comparison chart between the glass processed by process 1 and the reference glass. Fig. 9 This is a comparison between the glass treated by process 2 and the reference glass. There is no methyl orange solution residue on the surface of the treated glass, while there are more methyl orange solution droplets on the reference glass. It can be seen that the treated glass has a strong self-cleaning performance.
[0052] Example 2: Preparation of wear-resistant, self-cleaning, rain-resistant high-definition glass based on silicon nitride film The specific steps are as follows: (1) Ultraviolet laser is used to scan soda-lime glass to form a texture on the glass surface; the rated power of the laser is 5 W; the process parameters of laser scanning are: scanning speed 3 m / s; scanning line spacing 0.03 mm; frequency 30 KHz; pulse width 8 microseconds.
[0053] (2) A silicon nitride film was deposited on the glass that had been laser ablated in step (1) by using a magnetron sputtering coating system. A water-cooled silicon nitride target (99.995%) with a diameter of 60 mm was DC sputtered. The sputtering gas was pure Ar (99.9995%). The working gas pressure was 1.6 Pa. The argon gas flow rate was 30 sccm, the RF sputtering power was 60 W, the substrate heating temperature was 250 °C, and the deposition time was 2 min.
[0054] (3) Using ultraviolet laser to scan the surface of the soda-lime glass after the silicon nitride film is deposited in step (2), a rated power of 5W ultraviolet laser is used, the laser scanning frequency is 30KHz, the pulse width is 8 microseconds, the scanning speed is 3m / s, and the scanning line spacing is 0.1mm, thereby obtaining wear-resistant, self-cleaning, high-definition glass in rain.
[0055] The reference glass and the treated glass were respectively pressed under a 100g weight and dragged back and forth on 180-grit sandpaper for 5 times (the width of the sandpaper is 23cm in one stroke). Figure 10 shows the surface scratches and micron-level surface morphology information of the treated glass after rubbing on the sandpaper. The surface of the treated glass is widely distributed with circular pits of varying depths and diameters of about 40 microns. The stripes and circular pits are quasi-periodically distributed, and the surface scratches are shallower than those of the reference glass in Figure 1. Water was sprayed on the glass rubbed by sandpaper to simulate a scene in the rain and observe the clarity performance in the rain. Fig.11This is a comparison between the treated glass and the reference glass. Compared with the reference glass, the treated glass still has a clear field of vision, while the reference glass has many water droplets on its surface and the field of vision is blurred. The self-cleaning condition of the surface was observed by spraying methyl orange solution evenly on the glass surface rubbed by sandpaper and then spraying water to clean it. Fig.12 This is a comparison of the self-cleaning performance of the treated glass and the reference glass after sandpaper rubbing. There is no methyl orange solution residue on the surface of the treated glass, while there are more methyl orange solution droplets on the reference glass. It can be seen that the treated glass has a strong self-cleaning performance.
[0056] Example 3: Preparation of wear-resistant, self-cleaning, rain-resistant high-definition glass based on titanium carbide film The specific steps are as follows: (1) Ultraviolet laser is used to scan soda-lime glass to form a texture on the glass surface. The rated power of the laser is 5 W. The process parameters of laser scanning are: scanning speed 3 m / s; scanning line spacing 0.03 mm; frequency 30 KHz; pulse width 8 microseconds.
[0057] (2) A titanium carbide film was deposited on the glass that had been laser ablated in step (1) using a magnetron sputtering coating system. A water-cooled titanium carbide target (99.995%) with a diameter of 60 mm was DC sputtered. The sputtering gas was pure Ar (99.9995%). The working gas pressure was 1.6 Pa. The argon gas flow rate was 30 sccm, the RF sputtering power was 60 W, the substrate heating temperature was 250 °C, and the deposition time was 1 min.
[0058] (3) The glass surface after the titanium carbide film deposition in step (2) was scanned by ultraviolet laser. A 5W ultraviolet laser was used for laser scanning. Two process parameters were used. One was: frequency 30KHz, pulse width 8 microseconds, scanning speed 3m / s, scanning line spacing 0.1mm; the other was: frequency 30KHz, pulse width 8 microseconds, scanning speed 3m / s, scanning line spacing 0.8mm. Process 1 had a better effect, so it was used to measure the surface contact angle information. Wear-resistant, self-cleaning, rain-resistant high-definition glass was obtained.
[0059] The reference glass and the treated glass were respectively pressed under a 100g weight and rubbed back and forth on 180-grit sandpaper for 5 times (the width of the sandpaper is 23cm in one way). Figure 13 shows the surface scratches and micron-level surface morphology information of the glass treated by process 1 after rubbing on sandpaper, and Figure 14 shows the surface scratches and micron-level surface morphology information of the glass treated by process 2 after rubbing on sandpaper. Compared with the scratches on the reference glass in Figure 1, the scratches on the surface of the treated glass are shallower. Water was sprayed on the glass rubbed by sandpaper to simulate a scene in the rain and observe the clarity in the rain. Fig.15 This is a comparison chart of the clarity of the glass treated with process 1 after sandpaper abrasion and the reference glass after water spraying. Fig.16This is a comparison of the clarity of the glass treated by process 2 after sandpaper abrasion and the reference glass after water spraying. Compared with the reference glass, the field of view of the treated glass is still clear, while there are many water droplets on the surface of the reference glass and the field of view is blurred. Figure 17 shows the contact angle information of the glass treated by process 1 before and after sandpaper abrasion. The difference in the contact angle of the glass surface before and after sandpaper abrasion is very small, and it still maintains good hydrophilicity after sandpaper abrasion. Methyl orange solution is evenly sprayed on the surface of the glass abraded by sandpaper and then sprayed with water to observe its surface self-cleaning condition. Fig.18 This is a comparison chart between the glass processed by process 1 and the reference glass. Fig.19 This is a comparison between the glass treated by process 2 and the reference glass. There is no methyl orange solution left on the surface of the treated glass, while there are more methyl orange solution droplets left on the reference glass. It can be seen that the treated glass has a strong self-cleaning performance.
[0060] Example 4: Preparation of wear-resistant, self-cleaning, rain-resistant high-definition glass based on carbon film The specific steps are as follows: (1) Ultraviolet laser is used to scan soda-lime glass to form a texture on the glass surface; the rated power of the laser is 5 W; the process parameters of laser scanning are: scanning speed 3 m / s; scanning line spacing 0.03 mm; frequency 30 KHz; pulse width 8 microseconds.
[0061] (2) A carbon film was deposited on the glass that had been laser ablated in step (1) using a magnetron sputtering coating system. A water-cooled graphite target (99.995%) with a diameter of 60 mm was DC sputtered. The sputtering gas was pure Ar (99.9995%). The working gas pressure was 1.6 Pa. The argon gas flow rate was 30 sccm, the RF sputtering power was 60 W, the substrate heating temperature was 250 °C, and the deposition time was 1 min.
[0062] (3) The surface of the soda-lime glass after the carbon film deposition in step (2) is scanned by ultraviolet laser, with a rated power of 5 W, a laser scanning frequency of 30 kHz, a pulse width of 8 microseconds, a scanning speed of 3 m / s, and a scanning line spacing of 0.1 mm, to obtain wear-resistant, self-cleaning, high-definition glass in rain.
[0063] The reference glass and the treated glass were respectively pressed under a 100g weight and dragged back and forth on 180-grit sandpaper for 5 times (the width of the sandpaper is 23cm in one way). Figure 20 shows the surface wear marks and micron-level surface morphology information of the treated glass after rubbing on the sandpaper. Compared with the rubbed surface of the reference glass in Figure 1, the surface of the treated glass is widely distributed with circular pits of varying depths with a diameter of about 40 microns. The stripes and circular pits are quasi-periodic in distribution, and the surface wear marks are shallow.
[0064] Spray water on the glass rubbed by sandpaper to simulate the rain scene and observe the clarity in the rain. Fig.21This is a comparison picture between the treated glass and the reference glass. Compared with the reference glass, the field of vision of the treated glass is still clear, while there are many water droplets on the surface of the reference glass and the field of vision is blurred.
[0065] Evenly spray methyl orange solution on the glass surface rubbed by sandpaper and then spray water to clean it to observe the self-cleaning performance of the surface. Fig. 22 This is a comparison chart between the treated glass and the reference glass. There is no methyl orange solution residue on the treated glass surface, while there are more methyl orange solution droplets on the reference glass. It can be seen that the treated glass has a strong self-cleaning performance.
[0066] The above embodiments illustrate that by using equipment that can be mass-produced and adjusting process parameters, a micro-nano structure is formed on the glass surface, thus having the advantage of being mass-produced. The glass obtained by the above preparation method of the present invention has the characteristics of wear resistance, self-cleaning, and high clarity in rain, and can be used to produce glass that can be used in rain or underwater, such as front windshields, train and aircraft glass, medical endoscopes, and other glass that can be used in rain or underwater.
[0067] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for a person skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to replace some of the technical features therein by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions claimed to be protected by the present invention.
Claims
1. A method for preparing wear-resistant, self-cleaning, high-definition glass in rain, characterized in that: The following steps are involved: (1) Preparing surface texture on the glass surface; (2) Deposition of hard film on glass surface texture; (3) Laser scanning the glass surface after the hard film is deposited in step (2) to obtain wear-resistant, self-cleaning, high-definition glass in rain or underwater.
2. The method for preparing the wear-resistant, self-cleaning, rain-resistant high-definition glass according to claim 1, characterized in that: The step (1) can be achieved by a sol-gel method, a photolithography method, a reactive ion etching method, a laser ablation method, or a template method.
3. The method for preparing the wear-resistant, self-cleaning, rain-resistant high-definition glass according to claim 1, characterized in that: The glass includes all glass, glass that can be used in rain, and glass that can be used underwater.
4. The method for preparing the wear-resistant, self-cleaning, rain-resistant high-definition glass according to claim 1, characterized in that: The inorganic thin film includes at least one of silicon nitride film, silicon carbide film, carbon film, titanium carbide film, tungsten carbide film, aluminum nitride film, titanium nitride film and aluminum oxide film; the deposition thickness of the inorganic thin film is 1nm-500nm.
5. The method for preparing the wear-resistant, self-cleaning, rain-resistant high-definition glass according to claim 1, characterized in that: The deposition method includes magnetron sputtering, electron beam evaporation, atomic layer deposition, dip coating, slit coating, and roll-to-roll printing.
6. According to the method for preparing the wear-resistant, self-cleaning, high-definition glass in the rain as claimed in claim 1, the laser comprises an infrared laser, a visible light laser, an ultraviolet laser; at least one of a continuous laser and a pulsed laser.
7. The method for preparing the wear-resistant, self-cleaning, rain-resistant high-definition glass according to claim 1, characterized in that: The laser energy density is greater than 50 mJ / cm 2 .
8. The glass prepared according to claim 1 can be used for photovoltaic screens, solar glass, motorcycle glass, and glass that can be used in rain, underwater, and in body fluids.
9. The wear-resistant, self-cleaning, rain-resistant high-definition glass prepared by the preparation method according to any one of claims 1 to 8 and its application, characterized in that: The high-definition glass for use in rain or underwater can be used as the inner surface of glass, and can also be used as the outer surface of glass.